2016
DOI: 10.1186/s13071-016-1362-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, impact and control of bovine cysticercosis in Europe: a systematic review

Abstract: BackgroundBovine cysticercosis in Europe has been known for centuries but the data showing the occurrence of this zoonosis are scarce. The aim of this paper is to review and present the current knowledge on bovine cysticercosis in Europe.MethodsWe conducted a systematic review of studies published between 1990 and November 2014. Qualitative and quantitative data on prevalence, risk factors, burden and interventions were extracted and analysed.ResultsReports on prevalence were available for 23 European countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 49 publications
3
51
0
2
Order By: Relevance
“…A similarity can be observed comparing the prevalence assessed in this study with those reported in other countries, such as Iran (0·25%) (Khaniki et al 2010), Chile (0·58%) (Faustina et al 2012) and European countries (<1%) (Laranjo-González et al 2016). The no-detection of bovine cysticercosis in animals slaughtered from two municipalities does not mean a real absence of this disease at these areas due to the low sensitivity of the ongoing model of meat inspection and the practice of slaughter without inspection (illegal), which remains occurring in this state (Lopes et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…A similarity can be observed comparing the prevalence assessed in this study with those reported in other countries, such as Iran (0·25%) (Khaniki et al 2010), Chile (0·58%) (Faustina et al 2012) and European countries (<1%) (Laranjo-González et al 2016). The no-detection of bovine cysticercosis in animals slaughtered from two municipalities does not mean a real absence of this disease at these areas due to the low sensitivity of the ongoing model of meat inspection and the practice of slaughter without inspection (illegal), which remains occurring in this state (Lopes et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…However, the high variability of T. saginata cysticercus prevalence within and between European countries, with some national estimates ranging up to 6.2%, has also been described (Laranjo-González et al, 2016). The most recent UK-specific estimates describe a low prevalence; official government study results relating to cattle slaughtered between 2008 and 2011, state that 15 out of 190,493 calves (0.008%) and 2,674 out of 8,484,371 adult cows (0.032%) were found to be infected with T. saginata cysticercus at meat inspection (MLCS, 2013;Hill et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Laranjo- González et al (2016) highlight that the consumption of water contaminated with domestic sewage, the access to risky water with sewage treatment plant effluent in proximity, grazing next to streams and flooding on pastures were risk factors associated with cysticercosis occurrence, contributing to relations observed in this study. Furthermore, Kyvsgaard et al (1991) established that to allow cattle accesses to drink water from streams carrying effluent from sewage treatment was considered as risk factor for cysticercosis occurrence due to water sources overflow containing T. saginata eggs and consequently widespread eggs on grassland and on other water sources (Cabaret et al 2002).…”
Section: Discussionmentioning
confidence: 59%
“…Despite the disease's epidemiology is unraveled, more studies are necessary to identify new associated risk factors, to provide more substantial data for decision-making process in intervention procedures in order to reduce the disease's prevalence in endemic areas, and consequently reducing economic losses for beef production chain (Laranjo- González et al 2016).…”
Section: Introductionmentioning
confidence: 99%